Making Education Support Media About Flood Hazard in Samarinda in the Form of Digital Comic - Yustisi Calista Hartono; Rebecca Milka N.B.; Paulus Benny Setyawan (k@ta: A Biannual Publication on the Study of Languange and Literature, 2023)
Samarinda is the capital of East Kalimantan that is currently growing rapidly. However, the city of Samarinda still has a complex flood problem. This flood phenomenon occurs not only when it is the rainy season but also when it rains for 1-2 hours. This condition interferes with the activities of the community and the government in Samarinda in carrying out daily activities because it can immerse settlements and housing, damage public facilities, and cause casualties. Despite the frequent occurrence and inconvenience of the community, Samarinda's level of public awareness in preventing floods is still minimal. This can be seen from the large number of communities that still often throw garbage carelessly into rivers, especially residents living near rivers. The garbage thrown into the river hinders the flow of water to the point where it can create a high puddle. It is seen that there are many communities, especially young people who are open-minded about environmental issues. Therefore, it is necessary to design a flood prevention educational medium in Samarinda city that can start from oneself or a simple thing with the main target is Samarinda people itself, especially the youth with qualitative methods.